Experimental Investigation in Metacontingencies and Superstitious Practices: a way to more complex studies (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The investigation of social dynamics, specifically experimental studies on metacontingencies has encountered sometimes with patterns superstitious. This study was based on the Meta Model, created for a set of researches and accidentally produced a pattern superstitious. There was no selection of the desired pattern of interlocking contingencies. The consequence produced a cultural pattern superstitious in behavior of the participants, a fact which may suggest that patterns described superstitious, may have hindered the selection by metacontingencies. The investigation of superstitious behaviors, superstitious rules, as well as the effects of these operants in social dynamics, can be done in procedures like this, jointly composing a phenomenon of greater complexity.
Keywords: superstition; culture; metacontingencies